Evaluating diagnostic tests for bovine tuberculosis in the southern part of Germany: A latent class analysis. - Valerie-Beau Pucken; Gabriela Knubben-Schweizer; Dörte Döpfer; Andreas Groll; Angela Hafner-Marx; Stefan Hörmansdorfer; Carola Sauter-Louis; Reinhard K Straubinger; Pia Zimmermann; Sonja Hartnack (PLoS ONE)
Germany has been officially free of bovine tuberculosis since 1996. However, in the last years there has been an increase of bovine tuberculosis cases, particularly in the southern part of Germany, in the Allgäu region. As a consequence a one-time tuberculosis surveillance program was revisited with different premortal and postmortal tests. The aim of this paper was to estimate diagnostic sensitivities and specificities of the different tests used within this surveillance program. In the absence of a perfect test with 100% sensitivity and 100% specificity, thus in the absence of a gold standard, a Bayesian latent class approach with two different datasets was performed. The first dataset included 389 animals, tested with single intra-dermal comparative cervical tuberculin (SICCT) test, PCR and pathology; the second dataset contained 175 animals, tested with single intra-dermal cervical tuberculin (SICT) test, Bovigam® assay, pathology and culture. Two-way conditional dependencies were considered within the models. Additionally, inter-laboratory agreement (five officially approved laboratories) of the Bovigam® assay was assessed with Cohen's kappa test (21 blood samples). The results are given in posterior means and 95% credibility intervals. The specificities of the SICT test, SICCT test, PCR and pathology ranged between 75.8% [68.8-82.2%] and 99.0% [96.8-100%]. The Bovigam® assay stood out with a very low specificity (6.9% [3.6-11.1%]), though it had the highest sensitivity (95.7% [91.3-99.2%]). The sensitivities of the SICCT test, PCR, SICT test, pathology and culture varied from 57.8% [48.0-67.6%] to 88.9% [65.5-99.7%]. The prevalences were 19.8% [14.6-26.5%] (three-test dataset) and 7.7% [4.2-12.3%] (four-test dataset). Among all pairwise comparisons the highest agreement was 0.62 [0.15-1]). In conclusion, the specificity of the Bovigam® assay and the inter-laboratory agreement were lower than expected.